Prevalence of pain among female patients attending mobile medical camp in a rural block of Tamilnadu, India - V. V., Anantharaman; Muthunarayanan, Logaraj (International Journal Of Community Medicine And Public Health, 2017)
Background: Pain is a major global health problem and one of the most common problem for which people seek medical care. The musculoskeletal pains were not perceived by the health professionals as a serious health problem like other chronic non communicable diseases and pain is seen as a result of aging. The data on the prevalence of pain and musculoskeletal disorders in rural population of Tamilnadu, India is scare. The objective was to estimate the prevalence of different types of pain among female patients attending mobile medical camp in rural block in Tamilnadu, India. Methods: A cross-sectional study was carried out among 7124 female patients who attended our weekly mobile medical camp conducted in 30 villages selected conveniently in the rural block of Kancheepuram District of Tamil Nadu in the year 2013 and analyzed for the presence or absence types and site of pain (intermittent or continuous) for 1 month or longer. Results: Prevalence of pain was 62.8%. The prevalence of pain in <19 years was 29.5%, and 60 years and above was 73.1%. The most common pain reported was myalgia (18.3%), followed by headache (13.4%), low back pain (12.5%) and knee pain (9.3%). As the age advances the prevalence of myalgia, chest pain, knee pain, multiple joint pains also increases and it was found statistically significant. As the age advances the patients with pain symptoms also increases with 29.5% of the patients below the age 19 years to 74.5% of the patients above the age of 60 years. Conclusions: In conclusion more than 60% of the patients attending of the medical camp complained of pain. At primary care level the physicians needs better knowledge on the management of these common pains sites especially in the rural communities when people seek medical care through camps.